UTILIZATION OF TRADITIONAL GAMES AS TEACHING MATERIAL IN BIPA LEARNING - Aulia, Syafrida Reza; Aini, Alifia Nur; Hasanah, Dian Uswatun (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2024)
Congklak is a local culture that can be utilized as BIPA teaching material. There needs to be research on BIPA teaching materials regarding the game of congklak with local wisdom content that can be integrated with religious moderation. Therefore, researchers are interested in conducting research related to the traditional game of congklak which is associated with the principles of religious moderation in BIPA learning conducted at UIN Raden Mas Said Surakarta.  This research aims to examine the utilization of traditional games based on local wisdom and religious moderation as teaching materials. This research method uses a qualitative descriptive method. The data in this study are local wisdom-based materials using the traditional game of congklak with data sources in the form of documents and several references relevant to the research. The results showed that the conventional congklak game could be used as a fun and effective teaching material for BIPA learning because, in addition to being used as an introduction to Indonesian culture. It also contains at least seven values of religious moderation in the form of tawasuth, tawazun, I'tidal, tasamuh, musawah, syura, and ishlahKeywords: local wisdom, religious moderation, BIPA, teaching materials